An ontology-based knowledge model for software experience management - Mohameda, A.H.; Leeb, S.P.; Salim, S.S. (2004)
The efficient management of experience knowledge is vital in todayâs knowledge-based economy. This paper is concerned with proposing a model for software experience knowledge. The model is aimed to represent the backend of knowledge management tools that support organisational learning activities in a typical software organisation. Generic knowledge models have failed to produce good quality software experience management tools. The diversity in the types and forms of software experience knowledge makes it necessary to establish customised knowledge models to effectively accommodate such domain-specific knowledge. Our model extends the simple generic knowledge models that usually rely on non parameterised knowledge (i.e. free text) or that just reflect certain types of software experience knowledge (tacit or explicit). In contrast, our model aims to strike a delicate balance between explicit and tacit knowledge that in a way act as correlated information sources.